Biofuels, poverty, and growth: A computable general equilibrium analysis of Mozambique - Arndt, Channing; Benfica, Rui; Tarp, Finn; Thurlow, James; Uaiene, Rafael (International Food Policy Research Institute, 2008)
Large private investments in biofuels are presently underway in Mozambique. This paper uses an economywide model to assess the implications of these investments for growth and income distribution. Our results indicate that biofuels provide an opportunity to enhance growth and poverty reduction. Overall, the proposed biofuel investments increase Mozambique's annual economic growth by 0.6 percentage points and reduce the incidence of poverty by about six percentage points over the 12-year phase-in period. However, the benefits depend on production technology. Our results indicate that an outgrower approach to producing biofuels is more pro-poor, due to the greater use of unskilled labor and accrual of land rents to smallholders in this system, compared with the more capital-intensive plantation approach. Moreover, the expected benefits of outgrower schemes will be further enhanced if they result in technology spillovers to other crops.